A qualitative analysis exploring preferred methods of peer support to encourage adherence to a Mediterranean diet in a Northern European population at high risk of cardiovascular disease - Christina M. Erwin; Claire T. McEvoy; Sarah E. Moore; Lindsay Prior; Julia Lawton; Frank Kee; Margaret E. Cupples; Ian S. Young; Katherine Appleton; Michelle C. McKinley; Jayne V. Woodside (BMC, 2018)
Abstract Background Epidemiological and randomised controlled trial evidence demonstrates that adherence to a Mediterranean diet (MD) can reduce cardiovascular disease (CVD) risk. However, methods used to support dietary change have been intensive and expensive. Peer support has been suggested as a possible cost-effective method to encourage adherence to a MD in at risk populations, although development of such a programme has not been explored. The purpose of this study was to use mixed-methods to determine the preferred peer support approach to encourage adherence to a MD. Methods Qualitative (focus groups) and quantitative methods (questionnaire and preference scoring sheet) were used to determine preferred methods of peer support. Sixty-seven high CVD risk participants took part in 12 focus groups (60% female, mean age 64 years) and completed a questionnaire and preference scoring sheet. Focus group data were transcribed and thematically analysed. Results The mean preference score (1 being most preferred and 5 being least preferred) for group support was 1.5, compared to 3.4 for peer mentorship, 4.0 for telephone peer support and 4.0 for internet peer support. Three key themes were identified from the transcripts:1.Components of an effective peer support group: discussions around group peer support were predominantly positive. It was suggested that an effective group develops from people who consider themselves similar to each other meeting face-to-face, leading to the development of a group identity that embraces trust and honesty.2.Catalysing Motivation: participants discussed that a group peer support model could facilitate interpersonal motivations including encouragement, competitiveness and accountability.3.Stepping Stones of Change: participants conceptualised change as a process, and discussed that, throughout the process, different models of peer support might be more or less useful. Conclusion A group-based approach was the preferred method of peer support to encourage a population at high risk of CVD to adhere to a MD. This finding should be recognised in the development of interventions to encourage adoption of a MD in a Northern European population.